Marcadores moleculares de la progresión tumoral asociados a cadherina epitelial en cáncer de próstata y vejiga - Mencucci, María Victoria (2017)
Epithelial Cadherin (ECad) is a transmembrane glycoprotein that plays a main role in cell-cell adhesion. Ecad loss is a key event on Epithelial to Mesenchymal Transition (EMT), a process by which epithelial cells dramatic change in their molecular expression profile and acquire a motile and invasive behavior. These events lead to local invasion and distant metastasis, characteristics of tumor progression and aggressiveness.\nAn abnormal expression/function of ECad and other EMT-related molecules have been reported in Prostate Cancer (PC) and Bladder Cancer (BC) tumor progression, but studies are not conclusive. Moreover, there are molecules related to ECad and tumor aggressiveness that have not been studied in these tumors. Specifically, Dysadherin (Dys) has been found over-expressed in several solid tumors and associated with metastasis, but no studies have reported its expression in PC. Moreover, Ephrin-B1 has been related to ?-catenin deregulation and cell aggressiveness in other tumors, but no studies have reported its expression and function in BC.\nThe present study has thoroughly characterized the expression of ECad and other EMT-related molecules in PC and BC. Moreover, it is the first reporting expression of Dys in PC and Ephrin-B1 in BC, and their association with tumor progression and aggressiveness in these tumors.